Postnatal separation prevents the development of prenatal stress‐induced anxiety in association with changes in oestrogen receptor and oxytocin immunoreactivity in female mandarin vole (Microtus mandarinus) offspring. (19th December 2017) - He, Fengqin; Wang, Zijian; Guo, Guanlin
Abstract: Oestrogen has both anxiogenic and anxiolytic effects because of variation in opposing action on alpha (ERα) and beta (ERβ) estrogen receptors in the medial preoptic area (mPOA), bed nucleus of the stria terminalis (BNST) and medial amygdala (MeA). Oxytocin (OT) reverses some of the anxiogenic effects of oestrogen in the hypothalamic paraventricular nucleus (PVN) and supraoptic nucleus (SON). Because anxiety disorders are twice as common in women as in men, and oestrogen and OT are more important in females, we examined interactions between prenatal restraint stress (GS) and postnatal early short‐term maternal separation (MS) and female mandarin vole behaviour, estrogen receptors and OT. The results show that adult female offspring from GS/noMS mothers showed increased anxiety in open‐field and elevated plus‐maze tests and had lower serum 17‐beta‐oestradiol (E2 ) levels than female offspring from GS/MS, noGS/MS and noGS/noMS mothers. GS/noMS females had more immunoreactive neurons for ERα in several brain regions and less ERβ‐ and OT‐immunoreactive neurons in brain areas compared to GS/MS, noGS/MS and noGS/noMS offspring. Interestingly, noGS/MS and GS/MS offspring were similar to noGS/noMS offspring in that they did not develop anxiety as adults. We propose that MS alters the serum concentration of E2 and that the ERβ/ERα ratio and OT level in the brain may be responsible for the decrease in anxiety‐like behaviour in adult female offspring initially exposed to anxiety‐inducing conditions via an adverse foetal environment. Abstract : Postnatal early short‐term maternal separation (MS) alters the serum concentration of E2 and that the ERβ/ERα ratio and OT level in the brain may be responsible for the decrease in anxiety‐like behaviour in adult female offspring initially exposed to anxiety‐inducing conditions via an adverse foetal environment.